Industrial Structure, Environmental Pressure and Ecological Resilience of Resource-Based Cities-Based on Panel Data of 24 Prefecture-Level Cities in China - Chen, Yating; Wang, Hongmei (Frontiers in Environmental Science, 2022)
Based on 432 sets of data from three resource-based provinces in China, Anhui, Shanxi, and Sichuan, a fixed-effects model was established using panel data for empirical analysis to investigate the relationship between industrial structure, environmental pressure, and ecological resilience of resource-based cities, using entropy value method and principal component analysis to measure the industrial structure, environmental pressure and ecological resilience of resource-based cities. It is found that for resource-based cities, the economic growth mainly relies on the development of the secondary industry, which is primarily dependent on local natural resources. The empirical results show that the regional industrial structure has a significant negative impact on the cities’ ecological resilience, and the regional industrial structure has a significant positive effect on their environmental pressure. The article enriches the study of urban resilience theory and clarifies the relationship between industrial structure and environmental pressure on urban ecological resilience, which is of guiding significance to further promote the green development of resource-based cities.